Salt‐tolerant native plants have greater responses to other environments when compared to salt‐tolerant invasive plants. Issue 13 (19th June 2019) - Liu, Muxin; Liao, Huixuan; Peng, Shaolin
Abstract: The strong expansion potential of invasive plants is often attributed to fast adaptive responses to stress. However, the evolution of tolerance to one stressor may affect the responses to other stressors. Currently, it remains unclear what effect the evolution to one stressor might have on the responses to other single or combined stressors. Moreover, it is unknown how this might differ between invasive and native species. Invasive plants ( Mikania micrantha and Bidens pilosa ) and native plants ( Merremia hederacea and Sida acuta ) from low‐ and high‐salinity habitats were grown under control and stressful conditions [salt stress, water stress (drought/waterlogging), and their combinations]. We explored the effects of evolved salt tolerance on the responses to water stress/combined stresses and the underlying trait mechanisms. The high‐salinity populations of all species exhibited stronger salt tolerance than the low‐salinity populations. As to the tolerance to other stressors, the high‐salinity and low‐salinity populations of the invasive species were similar, whereas the high‐salinity populations of the native species exhibited stronger tolerance than the low‐salinity populations under most stress treatments. However, the enhanced salt tolerance in native species was accompanied by reduced total biomass under control condition. The stress tolerance of native species correlated with leaf production rate and allocation to root, while the performance of native species under control condition correlated with leaf morphology and carbon assimilation rate. This suggests a trade‐off between salt tolerance and performance in the native but not the invasive species, probably resulting from altered phenotypic/physiological traits. Synthesis: Our work suggests that the evolution of tolerance to one stressor may have stronger effects on the tolerance to other stressors of the native compared with the invasive species. This may be a new paradigm to explain the greater advantage of invasive vs. native species in highly stressful habitats. Abstract : Our work suggests that the evolution of tolerance to one stressor may have stronger effects on the tolerance to other stressors of the native compared with the invasive species. This may be a new paradigm to explain the greater advantage of invasive versus native species in highly stressful habitats.